2020
DOI: 10.1097/md.0000000000022105
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lymph node metastasis-related microRNAs in breast cancer using bioinformatics analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, supplementation with APE up-regulated three signaling pathways in CAM cells, namely, the NOD-like receptor signaling pathway, the PPAR signaling pathway, and the FoxO signaling pathway (Table S4). The NOD receptor signaling pathway is involved in cellular processes such as survival, proliferation, and activation . It has been found that the PPAR signaling pathway could participate in the myocyte proliferation process .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, supplementation with APE up-regulated three signaling pathways in CAM cells, namely, the NOD-like receptor signaling pathway, the PPAR signaling pathway, and the FoxO signaling pathway (Table S4). The NOD receptor signaling pathway is involved in cellular processes such as survival, proliferation, and activation . It has been found that the PPAR signaling pathway could participate in the myocyte proliferation process .…”
Section: Resultsmentioning
confidence: 99%
“…The NOD receptor signaling pathway is involved in cellular processes such as survival, proliferation, and activation. 45 It has been found that the PPAR signaling pathway could participate in the myocyte proliferation process. 46 The downstream signaling pathway of cell proliferation, the FoxO signaling pathway, also plays an important role in regulating cell proliferation, cell cycle, and oxidative stress.…”
Section: Proteomics Analysismentioning
confidence: 99%